PEMBANGUNAN MODAL INSAN DARI PERSPEKTIF PENGURUSAN ISLAM - Mansor, Fadillah; Tengku Kasim, Tengku Sarina Aini (Journal of Al-Tamaddun, 2008)
Development of human capital in management is one of the government growing concerns in The Ninth Malaysian Plan (RMK9). In order to address this concern, it is imperative to consider the effectiveness of employees and their subsequent relations to the quality of work. Development of human capital demands that workers around the world will be able not only to collaborate with one another, but also be competent to manage and solve more complex problems in daily working lives. From a different perspective, development of human capital is very significant in order to achieve the National Mission and Vision 2020. In terms of Islamic Management, the development of human capital has to be implemented to obtain the intended goal i.e. the development of effective package of human being as a holistic Muslim covering all aspects of life that are physical, spiritual, emotional and materialistic aspects. The holistic human capital development approach in developing human capital is determinant in achieving objectives and goals stated by the management of an organization. This article will discuss the important aspects in acquiring human capital form Islamic management perspective.